Yoga Education Program for Reducing Drug Dependency and Promoting Better Asthma Control for Chronic Asthmatic Children: A Multicity Experiment - Samta Pandya PhD (SAGE Publishing, 2019)
This article reports a 1-year long yoga education program (YEP) experiment aimed at reducing drug dependency and promoting better asthma control for chronic asthmatic children. Participants were 450 chronic asthmatic children across 4 cities. Two measures were used: Pediatric Asthma Diary (PAD) and Childhood Asthma Control Test (C-ACT). Results indicated that intervention group children had better asthma control in terms of lower average PAD scores and higher C-ACT scores and reduced drug intake vis-à-vis the control group. Within the intervention cohort, asthma symptoms persistence was lower and control was higher for children from Asian cities, boys, Hindus, middle-class children, those whose mothers were their primary caregivers, who lived in standard family setups, who also attended the optional YEP rounds, and regularly self-practiced. The strongest predictor of lower posttest PAD scores and higher C-ACT scores was self-practice. The YEP can be used as an effective complementary treatment for chronic asthmatic children.